PEREMPUAN DALAM TAFSIR; UPAYA PEMBACAAN FEMINIS TERHADAP TEKS-TEKS AGAMA - Nailun Najah; Zaglul Fitrian (IAIN Madura, 2021)
The interpretation about women that has been carried out by Muslim scholars can be mapped into three groups. First, traditional interpretation. Interpretation by using certain subjects according to the interests and abilities of the interpreter, such as fiqh, linguistics, history or sufism. Second, reactive interpretation. It is the reaction or response of modern thinkers to a number of obstacles experienced by women who are considered to come from the Qur'an. The problems discussed and the methods used often come from feminist and rationalist ideas, but without a comprehensive analysis of the verses in question. Third, holistic interpretation. This interpretation uses a comprehensive method of interpretation and relates it to various social, moral, economic, political issues, including women's issues that have emerged in the modern era. This article will discuss Muslim feminist interpretations, including Amina Wadud, Fatima Mernissi and Asghar Ali Engineer.